The neighbors and the police: The evaluation of police work from the perspective of residents of the periphery of Mar del Plata (Delito y Sociedad, 2023)
The objective of this article is to determine how citizens evaluate the police, and in particular the functional performance and the specific activity of police officers, within the framework of their daily experiences. To do this, we rely on the results of two surveys that we carried out in popular neighborhoods of Mar del Plata during 2021, and fifty interviews with residents of these same areas, who were questioned about different aspects of the security situation and the relationship with the police in their everyday experience. In line with the research results on Latin America, it is observed that there are relatively high levels of disapproval of the police service. This goes hand in hand with a moderate feeling of vulnerability. At the same time, there is a high demand for police presence, and for police action that meets the expectations of the population. But since neither this demand nor these expectations are satisfied, negative judgments tend to be made about the institution and its agents. This is not incompatible with the idea that the police have cultural, legal, budgetary, and political constraints to act as they should.
Keywords: police-citizen contact; legitimacy; police; security; citizenship